2016
DOI: 10.1002/2015jg003169
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting precipitation seasonality influences evapotranspiration dynamics in water‐limited shrublands

Abstract: Water‐limited ecosystems occupy nearly 30% of the Earth, but arguably, the controls on their ecosystem processes remain largely uncertain. We analyzed six site years of eddy covariance measurements of evapotranspiration (ET) from 2008 to 2010 at two water‐limited shrublands: one dominated by winter precipitation (WP site) and another dominated by summer precipitation (SP site), but with similar solar radiation patterns in the Northern Hemisphere. We determined how physical forcing factors (i.e., net radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 77 publications
(125 reference statements)
3
37
1
2
Order By: Relevance
“…However, the P was markedly high in August compared to the ET. This phenomenon regarding the role of temperature and P on ET was similar to some findings in previous studies [45,46]. Monthly variations in the ET were closely related to vegetation growth during the growing period in this region; in 2013 and 2015, the ET rapidly increased with vegetation growth from April to July and reached its maximum value in July.…”
Section: Land-atmosphere Water Exchange In the Growing Seasonsupporting
confidence: 75%
“…However, the P was markedly high in August compared to the ET. This phenomenon regarding the role of temperature and P on ET was similar to some findings in previous studies [45,46]. Monthly variations in the ET were closely related to vegetation growth during the growing period in this region; in 2013 and 2015, the ET rapidly increased with vegetation growth from April to July and reached its maximum value in July.…”
Section: Land-atmosphere Water Exchange In the Growing Seasonsupporting
confidence: 75%
“…Recent research has revealed that interannual precipitation and temperature variations predominantly control variations in regional ET and hydrological cycles in many parts of these water‐limited regions [ Gao et al ., ; Goyal , ; Liu and Yang , ; K. Wang et al ., ]. Variations in other climate factors, such as soil moisture availability [ Villarreal et al ., ], solar radiation [ S. Y. Zhang et al ., ], vapor‐pressure deficits, and wind speed [ Burn and Hesch , ], also play an important role in mediating regional spatial and temporal ET patterns. In addition, changes in vegetation growth affect ET through their regulatory effects on land‐surface roughness, albedo, and water interception [ Shen et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…On one side, MexFlux sites have contributed to synthesis studies to better understand the role of water‐limited ecosystems across North America (Biederman et al, ; Villarreal et al, ). On the other side, the lack of coordination on the distribution of MexFlux sites has resulted in a lack of representativeness for monitoring GPP and ET at the national level (Figures d and d and Table ).…”
Section: Discussionmentioning
confidence: 99%